THE IMPACT OF ASSISTANCE FROM THE BARRU DISTRICT FISHERIES SERVICE IN THE FRAMEWORK OF INCREASING THE PRODUCTIVITY OF TAMBAK CULTIVATION IN LASITAE VILLAGE, TANETE RILU SUB-DISTRICT, BARRU DISTRICT - Jumria; A.Aminah; Muhammad, Mukmin (Meraja journal, 2022)
[Full Paper] to pdf Copyright (c) 2022 Meraja journal